Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Focusing quorum sensing signalling by nano‐magnetic assembly - Yongguang Guan; Chen‐Yu Tsao; David N. Quan; Ying Li; Lei Mei; Yingying Song; Boce Zhang; Yi Liu; Gregory F. Payne; William E. Bentley; Qin Wang (Environmental Microbiology, 2018)
Summary Quorum sensing (QS) exists widely among bacteria, enabling a transition to multicellular behaviour after bacterial populations reach a particular density. The coordination of multicellularity enables biotechnological application, dissolution of biofilms, coordination of virulence, and so forth. Here, a method to elicit and subsequently disperse multicellular behaviour among QS‐negative cells is developed using magnetic nanoparticle assembly. We fabricated magnetic nanoparticles (MNPs, ∼5 nm) that electrostatically collect wild‐type (WT) Escherichia coli BL21 cells and brings them into proximity of bioengineered E. coli [CT104 (W3110 lsrFG − luxS − pCT6 + pET‐DsRed)] reporter cells that exhibit a QS response after receiving autoinducer‐2 (AI‐2). By shortening the distance between WT and reporter cells (e.g., increasing local available AI‐2 concentrations), the QS response signalling was amplified four‐fold compared to that in native conditions without assembly. This study suggests potential applications in facilitating intercellular communication and modulating multicellular behaviours based on user‐specified designs.

Evolution of interspecies unilateral incompatibility in the relatives of Arabidopsis thaliana - Ling Li; Bo Liu; Xiaomei Deng; Hainan Zhao; Hongyan Li; Shilai Xing; Della D. Fetzer; Mengya Li; Mikhail E. Nasrallah; June B. Nasrallah; Pei Liu (Molecular Ecology, 2018)
The evolutionary concurrence of intraspecies self‐incompatibility ( SI ) and explosive angiosperm radiation in the Cretaceous have led to the hypothesis that SI was one of the predominant drivers of rapid speciation in angiosperms. Interspecies unilateral incompatibility ( UI ) usually occurs when pollen from a self‐compatible ( SC ) species is rejected by the pistils of a SI species, while the reciprocal pollination is compatible ( UC ). Although this SI × SC type UI is most prevalent and viewed as a prezygotic isolation barrier to promote incipient speciation of angiosperms, comparative evidence to support such a role is lacking. We show that SI × SI type UI in SI species pairs is also common in the well‐characterized accessions representing the four major lineages of the Arabidopsis genus and is developmentally regulated. This allowed us to reveal a strong correlation between UI strength and species divergence in these representative accessions. In addition, analyses of a SC accession and the pseudo‐self‐compatible ( psc ) spontaneous mutant of Arabidopsis lyrata indicate that UI shares, at least, common pollen rejection pathway with SI . Furthermore, genetic and genomic analyses of SI × SI type UI in A. lyrata × A. arenosa species pair showed that two major‐effect quantitative trait loci are the stigma and pollen‐side determinant of UI , respectively, which could be involved in heterospecies pollen discrimination. By revealing a close link between UI and SI pathway, particularly between UI and species divergence in these representative accessions, our findings establish a connection between SI and speciation. Thus, the pre‐existence of SI system would have facilitated the evolution of UI and accordingly promote speciation.

Overexpression of VpPR10.1 by an efficient transformation method enhances downy mildew resistance in V. vinifera - Hang Su; Yun-Tong Jiao; Fang-Fang Wang; Yue-E Liu; Wei-Li Niu; Guo-Tian Liu; Yan Xu (Plant Cell Reports, 2018)

In vitro prebiotic effects of seaweed polysaccharides - Xiaolin Chen; Yuhao Sun; Linfeng Hu; Song Liu; Huahua Yu; Rong’e Xing; Rongfeng Li; Xueqin Wang; Pengcheng Li (Journal of Oceanology and Limnology, 2018)

Long-term (≥20 years) application of fertilizers and straw return enhances soil carbon storage: a meta-analysis - Yu’e Li; Shengwei Shi; Muhammad Ahmed Waqas; Xiaoxia Zhou; Jianling Li; Yunfan Wan; Xiaobo Qin; Qingzhu Gao; Shuo Liu; Andreas Wilkes (Mitigation and Adaptation Strategies for Global Change, 2018)

Transient receptor potential vanilloid-3 (TRPV3) activation plays a central role in cardiac fibrosis induced by pressure overload in rats via TGF-β1 pathway - Yan Liu; Hanping Qi; Mingyao E; Pilong Shi; Qianhui Zhang; Shuzhi Li; Ye Wang; Yonggang Cao; Yunping Chen; Lina Ba; Jingquan Gao; Wei Huang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Reduced deep regional cerebral venous oxygen saturation in hemodialysis patients using quantitative susceptibility mapping - Chao Chai; Saifeng Liu; Linlin Fan; Lei Liu; Jinping Li; Chao Zuo; Tianyi Qian; E. Mark Haacke; Wen Shen; Shuang Xia (Metabolic Brain Disease, 2018)